Emergence of multiple genotypes of H5N1 avian influenza viruses in Hong Kong SAR - Guan, Y. (National Academy of Sciences, 2002)
Although A/Hong Kong/156/97 (H5N1/97)-like viruses associated with the “bird flu” incident in Hong Kong SAR have not been detected since the slaughter of poultry in 1997, its putative precursors continue to persist in the region. One of these, Goose/Guangdong/1/96 (H5N1 Gs/Gd)-like viruses, reassorted with other avian viruses to generate multiple genotypes of H5N1 viruses that crossed to chickens and other terrestrial poultry from its reservoir in geese. Whereas none of these recent reassortants had acquired the gene constellation of H5N1/97, these events provide insight into how such a virus may have been generated. The recent H5N1 reassortants readily infect and kill chicken and quail after experimental infection, and some were associated with significant mortality of chickens within the poultry retail markets in Hong Kong. Some genotypes are lethal for mice after intra-nasal inoculation and spread to the brain. On this occasion, the early detection of H5N1 viruses in the retail, live poultry markets led to preemptive intervention before the occurrence of human disease, but these newly emerging, highly pathogenic H5N1 viruses provide cause for pandemic concern.